Measurement of τ polarisation at LEP - Dova, María Teresa (2003)
Using the data collected with the L3 detector at LEP between 1990 and 1995, corresponding to an integrated luminosity of 149 pb−1, the τ longitudinal polarisation has been measured as a function of the production polar angle using the τ decays τ−→h−ντ (h=π,ρ,a1) and <mtext>τ</mtext>−<mtext>→ℓ</mtext>−<mtext>ν</mtext><mtext>̄</mtext>ℓ<mtext>ν</mtext>τ (ℓ=e,μ). From this measurement the quantities Ae and Aτ, which depend on the couplings of the electron and the τ to the Z, are determined to be Ae=0.1678±0.0127±0.0030 and Aτ=01540±0.0088±0.0062, consistent with the hypothesis of e–τ universality. Under this assumption a value of <mtext>A</mtext>ℓ<mtext>=0.1540±0.0074±0.0044</mtext> is obtained, yielding the value of the effective weak mixing angle <mtext>sin</mtext>2<mtext>θ</mtext><mtext>W</mtext><mtext>=0.2306±0.0011</mtext>.